Documenting the Sporangium Development of the Polypodiales Fern Pteris multifida - Yang, Nai-Ying; Jia, Xin-Lei; Sui, Chang-Xu; Shen, Shi-Yi; Dai, Xi-Ling; Xue, Jing-Shi; Yang, Zhong-Nan (Frontiers in Plant Science, 2022)
Reconstructing the development of sporangia in seed-free vascular plants provides crucial information about key processes enabling the production of spores that are important in the life cycle of these plants. By applying fluorescence imaging in intact tissues using dyes and confocal microscopy, this study aimed to reconstruct the key steps during the development of sporangia. Special emphasis was taken on the cell wall structures of tapetum and spore mother cells that have been challenged by microscopical documentation in the past. After staining the cell wall and cytoplasm using calcofluor white and basic fuchsin, the sporangium development of Pteris multifida was observed using confocal microscopy. The clear cell lineages from the sporangial initial cell to stalk, epidermis, inner tapetum, outer tapetum, and sporogenous cells were revealed by confocal imaging. The sporangium development improved in this work will be useful for a general understanding of fern spore formation.